FOXA1 Suppresses SATB1 Transcription and Inactivates the Wnt/β-Catenin Pathway to Alleviate Diabetic Nephropathy in a Mouse Model - Zhu H; Peng J; Li W (Diabetes, Metabolic Syndrome and Obesity, 2021)
Hong Zhu,* Jiarui Peng,* Wei Li Department of Endocrinology, The Third People’s Hospital of Yunnan Province, Kunming, 650011, Yunnan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei LiDepartment of Endocrinology, The Third People’s Hospital of Yunnan Province, No. 292, Beijing Road, Guandu District, Kunming, 650011, Yunnan, People’s Republic of ChinaTel/Fax +86-871-63194278Email Liwei813_2@126.comObjective: Diabetic nephropathy (DN) represents the most common diabetic complication that may lead to end-stage renal disease. This work focused on the effect of FOXA1 on the DN development and the molecular mechanism.Methods: A mouse model of DN was induced by high-fat diets and streptozotocin. The concentrations of blood glucose and urinary protein in mice, and the pathological changes in mouse kidney tissues were determined. A podocyte cell line MPC-5 was treated with high glucose (HG) to mimic a DN-like condition in vitro. FOXA1 and SATB1 were overexpressed in HG-treated MPC-5 cells and in DN mice to explore their effects on cell proliferation and apoptosis, and on pathological changes in mouse kidney tissues. The binding relationship between FOXA1 and STAB1 was predicted and validated. Activation of the Wnt/β-catenin pathway was detected.Results: FOXA1 was poorly expressed in the kidney tissues of DN mice. Overexpression of FOXA1 reduced the concentrations of fasting blood glucose and 24-h urinary protein in mice. It also suppressed the accumulation of glomerular mesangial matrix and hyperplasia of glomerular basement membrane, and reduced collagen deposition and interstitial fibrosis in mouse kidney. Also, FOXA1 reduced HG-induced apoptosis of MPC-5 cells. FOXA1 bound to the promoter region of SATB1 for transcription suppression. Overexpression of SATB1 activated the Wnt/β-catenin pathway and blocked the protective roles of FOXA1 in DN mice and in HG-treated MPC-5 cells.Conclusion: This study demonstrated that FOXA1 transcriptionally suppresses SATB1 expression and inactivates the Wnt/β-catenin signaling pathway, thereby inhibiting podocyte apoptosis and DN progression.Keywords: diabetic nephropathy, FOXA1, SATB1, Wnt/β-catenin, MPC-5